N3LO NN interaction adjusted to light nuclei in ab exitu approach - A.M. Shirokov; I.J. Shin; Y. Kim; M. Sosonkina; P. Maris; J.P. Vary (Physics Letters B, 2016)
We use phase-equivalent transformations to adjust off-shell properties of similarity renormalization group evolved chiral effective field theory NN interaction (Idaho N3LO) to fit selected binding energies and spectra of light nuclei in an ab exitu approach. We then test the transformed interaction on a set of additional observables in light nuclei to verify that it provides reasonable descriptions of these observables with an apparent reduced need for three- and many-nucleon interactions.